"He'd mind you, you mind him": Experiences of end of life care for people with an intellectual disability as perceived by staff carers. - Mc Carron, Mary; Burke, Eilish (School of Nursing and Midwifery, Trinity College Dublin, 2017)
Life expectancy for people with an intellectual disability (ID) is increasing (Kelly & Kelly 2013), providing new challenges in understanding not only how people are living with illness but also how they are dying. While there is a growing openness to death, end of life planning and palliative care in the general population, the limited research available suggests that a similar trend has not been witnessed for the population with an intellectual disability (Bailey et al., 2016; Todd, 2005; Tuffrey-Wijne et al., 2006). With additional issues of communication difficulties, limited capacity, and a high prevalence of dementia, end of life care for people with intellectual disability is complex (Kirkendall et al., 2016; McCallion et al., 2012; McCarron et al., 2013; Wiese et al., 2012a). Indeed, carers frequently report that delivering high quality end of life care for people with intellectual disability is an important, if unrecognised, element of their work (Todd, 2013); and one for which they sometimes feel inadequately prepared (Ryan et al., 2011; Bailey et al., 2016). Despite these known challenges, as well as a growing population of people with an intellectual disability requiring end of life care, there is as of yet too little investigation of: The demographic profile, health status, and disease patterns reported by adults with intellectual disability at end of life; The healthcare utilisation and health care service needs of this population; The experiences of people with intellectual disabilities and those of their carers during the last days of their lives
PUBLISHED
Keywords: Ageing; Ageing, Health and Intellectual Disability; Age-related disability; Intellectual Disability; Mental Health/Psychosocial disability